Multi-functional bioactive secondary metabolites derived from endophytic fungi of marine algal origin - Harikrishnan M; Saipriya P. P; Prabha Prakash; C. Jayabaskaran; Sarita G. Bhat (Current Research in Microbial Sciences, 2021)
Endophytic fungi from marine macroalgae are endowed with various pharmacologically active metabolites. This study mined, identified and screened endophytic fungi (EF) isolated from marine algae from the west coast of South India for screening anticancer, antioxidant and antimicrobial secondary metabolite producers. Five EF isolated from sampled marine algae were identified using morphology and ITS based identification as Grammothele fuligo, Rigidoporus vinctus, Cystobasidium minutum, Candida railenensis and Pichia kudriavzevii. After culturing 20 days on PDA medium, the ethyl acetate extracts of Cystobasidium minutum showed potent antimicrobial activity against P. aeruginosa with an IC50 value of 458.7 ± 1.021 µg/mL whereas Pichia kudriavzevii extracts showed promising antioxidant activity (IC50 value of 65.78 ± 1.082 µg/mL, 38.74 ± 1.040 µg/mL and 32.01 ± 1.018 µg/mL for DPPH assay, ABTS assay and FRAP assay respectively) and high cytotoxic activity against MG63 cell line (IC50 = 145.1 ± 1.086 µg/mL, no activity against U87 cells). The phytochemical screening of the extracts unveiled the existence of diverse groups of secondary metabolites. Further, Gas Chromatography Mass Spectroscopy (GC-MS) analysis of the extract revealed the presence of compounds that are known to be antibacterial, antioxidant and cytotoxic. These results indicate that marine derived endophytes could be potent sources for multi-functional bioactive compounds and may find prospective application in pharmaceutical industry.